Using diffusion of innovation theory to understand how technology is adopted in mathematics at a South African higher education institution - Chizwina, Sabelo R (School of Education, 2016)
The issue of students enrolling who are ill prepared in mathematics for university studies has been an area of concern for some time in South Africa. Various universities tried different interventions to address this problem. One example is the establishment of a bridging programme at an institution of higher learning. Technology has been discussed as support that can be provided to students. This study therefore sought to understand the adoption of technology in the teaching of mathematics at an institution of higher education in South Africa. Using Roger's diffusion of innovation theory, this study sought to understand how technology is adopted by mathematics teachers in the bridging programme. Whilst the results of the study show that some teachers have adopted technology at different scales to provide access, to supplement instruction and to encourage interaction, the results also show that some teachers are uncertain of the benefits that technology has to teaching and learning in the programme. The current talk and chalk method is seen as being essential as it is tried and tested. The study also showed that teachers did not receive support from the institution resulting in them seeking assistance from outside of the university. The study recommends that higher education institutions should provide instructional design support to ensure that teachers are not overburdened with developing technology interventions where they have little or no expertise in.